(untitled) (Scientific journal of the Fergana State University, 2024)
This article provides information on the main chemical composition of the leaves and roots of pepper growing in Fergana region, as well as the methods of its use in medicine. According to the results of the research, it is possible to see glycosylate and fatty acids and phenolic acids in the root part of the pepper plant, and many vitamins and carotene in the leaf part. In folk medicine, it is mainly used as a medicine for: Tracheitis, bronchitis, persistent cough, as well as cystitis and urethritis. The juice made from fresh roots contains lysozyme enzyme with antimicrobial activity and thiamin, riboflavin, carotene, starch, carbohydrates (74%) and resinous substances. The leaves contain 240-350 mg %, and the root contains 120-250 mg % ascorbic acid. Carotene and alkaloids were found in the leaves; The seeds contain oil and alkaloids, which can be used to prepare various biologically active supplements.